Menanamkan Kejujuran Sejak Dini: Kajian Kualitatif terhadap Pendidikan Karakter Jujur Berbasis Kisah Nabi dan Rasul - Kafa Sakinah; Rudi Hartono; Wido Supraha (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Instilling the value of honesty from an early age is a fundamental step in shaping the character of a child who is resilient and moral. This study aims to qualitatively examine the effectiveness of honest character education based on the stories of the Prophet and Apostle in instilling the value of honesty in early childhood. The method used is a descriptive qualitative study with data collection techniques through observation, in-depth interviews with teachers, and documentation of learning activities. The results of the study show that the use of the stories of Prophets such as the Prophet Muhammad SAW, Prophet Ibrahim AS, and Prophet Yusuf AS as role models is very effective in strengthening children's understanding of the importance of honesty. In addition, the storytelling method has been proven to attract children's interest and make it easier to internalize moral values. The implications of these findings indicate the importance of integrating the material of the Prophet and Messenger's story in the character education curriculum at the early childhood education level.